Identificação de altas capacidades em estudantes estrangeiros do ensino superior - Oliveira, Ana Paula Santos (2020)
The National Policy of Special Education in the Perspective of Inclusive Education define as the target audience of Special Education students with disabilities, global developmental disorders and high ability or giftedness. High ability students are those who demonstrate high potential in any of these areas, isolated or combined: intellectual, academic, leadership, psychomotricity, creativity and arts. The document of the aforementioned Policy explains that attendance this public is a transversal modality at all levels and modalities of education. However, there is a large gap in the specialized literature in relation to the identification of high abilities when refers to higher education and even more scarce when refers to foreign students, in view of this scenario, the present research, had as main goal to identify evidence of high abilities in foreign students of Hispanic origin, in higher education. The research was configured as descriptive, with a qualitative approach. The participants were sixteen (16), with eight (8) foreign students regularly enrolled in higher education undergraduate or postgraduate courses, from two public universities in the interior of São Paulo (P1, P2, P3, P4, P5, P6, P7 and P8), and eight (8) people closest to the foreign students, as a second source (F1, F2, F3, F4, F5, F6, F7 and F8). The instruments used were four (4): Cuestionario Para Identificación De Indicadores De Altas Habilidades/Superdotación – Adultos; Cuestionario Para Identificación De Indicadores De Altas Habilidades/Superdotación - Adultos - 2ª Fuente; Questionário Para Identificação De Indicadores De Altas Habilidades/Superdotação Adulto - 2ª Fonte; Cuestionario de Detección de Las Inteligencias Múltiples and a complementary questionnaire created by the researcher. Summarizing the results and triangulating the data, it was indicated only one participant, P2, who reached the minimum established scores of 70% in all instruments. More specifically, the participant was indicated in the instrument Cuestionario de Detección de Las Inteligencias Múltiples in the Intelligence Musical; Linguistics; Spatial and Intrapersonal Intelligence. In the Cuestionario Para Identificación De Indicadores De Altas Habilidades/Superdotación she was indicated by her second source with a total score of 70% (49 frequent answers) and selfindication, also, with a score of 70% (51 frequent answers). This result represents a percentage of 12.5% of the research sample, which is in line with the specialized literature. The questionnaire developed by the researcher was crucial to complement the indication of the participant with high abilities indicators, showing her profile in the academic area.